Petempatan masyarakat zaman logam di Selangor berdasarkan data arkeologi - Zuliskandar Ramli,; Nik Hassan Shuhaimi Nik Abdul Rahman, (Universiti Kebangsaan Malaysia, 2010)
The existence of early settlements in Selangor during the Metal Age about 2500 years ago in Selangor has been proven by the discovery of metal artifacts which have been found accidentally or through archaeological excavations. These settlements are mostly located near rivers and expanded from the Neolithic culture. Among the important rivers used as settlement sites of the metal age society are Bernam River, Langat River, Sedu River, Klang and Semenyih. These rivers acted as the main communication route between the lowland people and inland community and also a place where people finds food. The river valleys in Selangor are rich in natural resources such as tin and this factor enabled local communities to establish relationships with people outside the community, especially in the northern peninsula as well as traders from Vietnam. This is necessary because tin is needed to produce bronze products. Barter trade was carried out where tin was traded for luxurious items made from bronze such as bronze drums and bronze bells, beads and pottery. Bronze drums and bronze bells were regarded as status symbols for the local community leaders. Kampung Sungai Lang, Jenderam Hilir, Sidu and Klang River Valley are sites where several bronze artifacts were found. These sites became evident of the development of local community, from community that practice Neolithic socio-culture to more advanced community that used metal in their culture and belief system. The main factor for this development is contact with international traders